The Reason for The Increase in Digital Gold Investment Preferences Among Semarang City Residents - Yeni Wijayanti; Theresia Tyas Listyani; Mirasanti Wahyuni (Politeknik Negeri Semarang, 2025)
The purpose of this study is to analyze the influence of knowledge, trust, motivation, and risk perception on the digital gold investment preferences of the people of Semarang City. The study sample consisted of 137 respondents from diverse demographic backgrounds in Semarang City. The methods used include validity testing, reliability testing, normality testing, classical assumption testing, and multiple linear regression analysis to ensure the accuracy and reliability of the results. The F-test and t-test results show that simultaneously, the variables of knowledge, trust, motivation, and risk perception significantly affect digital gold investment preferences. However, partially only trust and risk perception have a significant positive effect on these preferences. Knowledge has a significant negative effect, while motivation shows no significant influence. These findings indicate that building investor trust and managing risk perception are the key strategies to increase the interest and preference of the community in investing in digital gold. On the other hand, improving knowledge needs to be supported by a more effective educational approach to encourage positive and sustainable investment behavior.